Cold storage demand for Rocha pear ripening: A comparison between a shorter and a longer cold period - Dias, Cindy (2022)
'Rocha' pear is a cultivar that when harvested at the recommended maturity stage (physiological condition that allows resisting to prolong cold storage), requires chilling exposure after harvest, to induce an autonomously ripening appreciated by the consumer. Fruit were stored immediately after harvest, for 6 d (batch 1) or 26 d (batch 2), in normal cold atmosphere storage, to further our understanding of 'Rocha' pear ripening under different short cold storage durations. The ripening events were then monitored at 0, 3, 7, and 10 d of shelf-life at room temperature (± 20 °C) through physicochemical and biochemical changes, including firmness, soluble sugars, malic acid, esters profile, and ethylene metabolism (1-aminocyclopropane-1-carboxylic acid (ACC) and 1-aminocyclopropane-1-carboxylic acid oxidase (ACO)). We found that ripening behaviour upon rewarming from both cold storage periods was similar, with fruit ripening with a typical pattern of ethylene production and respiration rates concomitant with a higher ACO activity. Soluble sugar and esters emission were not influenced by cold storage duration, but interestingly butyl acetate levels were significantly higher on pear, which was cold stored for 26 d Our data provide more novel information about Rocha' pear's ripening physiology, indicating for the first time that approximately one week of chilling temperature is enough to promote ripening rate processes. Such knowledge could be an asset to the efficient management of 'Rocha' pear storage.